Geothermal Energy Potential In Supporting National Defense And Economic Sustainability In Developing Countries - Inez Koerniawati; Lukman Yudho Prakoso; Rheviany HS Putri; Nur Khotimah (PT. Publikasiku Academic Solution, 2023)
In recent decades, geothermal energy has become increasingly important as an alternative energy source that can support national energy security and economic sustainability in developing countries. This article discusses the potential of geothermal resources and their implications for national defense and economic sustainability in developing countries. The author presents an overview of the potential of geothermal energy in developing countries and then discusses its implications for national defense and economic sustainability. This article also discusses the challenges and opportunities faced by developing countries in harnessing the potential of geothermal energy to strengthen energy security and support economic growth. The method used in this research is literature analysis and case studies. Data was collected from sources such as official government reports, academic studies, and scientific journal articles. The results of the study show that geothermal energy has great potential in supporting national defense and economic sustainability in developing countries. However, there are still many challenges to be overcome in developing the geothermal energy industry, including difficulties in identifying geothermal resource potential and building the necessary infrastructure to harness it. Nevertheless, this article shows that geothermal energy can be a promising solution for developing countries to strengthen energy security and support sustainable economic growth.